Accurate chiral pattern recognition for amines from just a single chemosensor. Issue 15 (6th March 2020) - Sasaki, Yui; Kojima, Soya; Hamedpour, Vahid; Kubota, Riku; Takizawa, Shin-ya; Yoshikawa, Isao; Houjou, Hirohiko; Kubo, Yuji; Minami, Tsuyoshi
Abstract : The current work proposes a novel method for accurate pattern recognition of (mono- and di-) amines and determination of enantiomeric excess (ee) using molecular self-assembly. Abstract : The current work proposes a novel determination method for enantiomeric excess (ee) in (mono- and di-) amines using molecular self-assembly. A pyridine-attached binaphthyl derivative (( R )-1 ) exhibits fluorescence responses based on imine formation between the aldehyde group of ( R )-1 and target chiral amines ( i.e. cyclohexane diamine (CHDA ), 2-amino-1, 2-diphenylethanol (ADPE ), 1, 2-diphenylethylenediamine (DPDA ), 1-amino-2-indanol (AID ), and leucinol ) in the presence of zinc(ii ) ions (Zn 2+ ). Because of the multi-optical responses which are derived from the variation of chiral complexes, pattern recognition-based discrimination ( i.e. linear discriminant analysis (LDA)) has been achieved for five types of enantiomeric pairs of amines. Possessing such a discrimination capability in combination with data processing (LDA and an artificial neural network) allows accurate determination (prediction error < 1.8%) of the % ee of individual targets such as CHDA which is one of the main components of pharmaceutical drugs. The simple molecular self-assembled system enabled simultaneous multi-chiral discrimination and % ee determination of unknown samples.